Experiential function analysis of signposts in recreational tourism at Nusa Lima Beach - Harefa, Afore Tahir; Zebua, Feliks Rejeki Sotani; Zamasi, Martin Ifolala (Institute of Computer Science (IOCS), 2024)
This research aims to analyze the experiential function of signposts at Nusa Lima Beach using a Functional Grammar approach. The study employs a qualitative method, emphasizing the understanding of meanings and experiences conveyed through language. The primary data source consists of sentences found on the signposts at Nusa Lima Beach, which were documented and transformed into full sentences for detailed analysis. The research was conducted through direct observation and documentation, ensuring comprehensive data collection. The Functional Grammar approach, developed by Michael Halliday, was utilized to analyze the experiential meaning within the ideational function of language. The findings reveal how the signposts' sentences communicate tourism experiences and their linguistic structure's function and purpose. The study concludes that the language used in these signposts effectively enhances the tourist experience by reflecting physical, mental, and relational experiences. The implications of this research extend to beach managers, providing insights for designing engaging and effective signage, and contribute to the academic field by bridging linguistics and tourism studies, demonstrating the utility of Functional Grammar in analyzing real-world language use in tourism contexts.